Ultimate strength of horizontally curved steel I-girders with equal end moments. (15th December 2017) - Lee, Keesei; Davidson, James S.; Choi, Junho; Kang, Youngjong
Highlights: Bending-torsion interaction can affect the strength of horizontally curved member. This paper introduces a new concept, termed "Lateral Torsional Vertical Behavior". Three main factors that affect ultimate strength for curved members are demonstrated. A strength equation for curved I-girders subjected to pure moment is suggested. Abstract: Even under gravitational loading alone, horizontally curved girders experience not only bending moment but also torsional moment. The torsional moment acting on open sections simultaneously produces shear and normal stress due to pure and warping torsion respectively. Consequently, bending moment, pure torsion and warping torsion are coupled, which results in a very complicated stress state that makes it difficult to calculate the ultimate strength of horizontally curved members. This study revealed that the initial curvature can reduce the ultimate strength of horizontally curved members by up to 50%. Although current design specifications such as the AASHTO LRFD Bridge Design Specifications, suggest some alternatives, the exact behavior of a curved member cannot be considered well with those provisions. While it is true that the one-third rule is convenient to apply and gives good results, there is no strength equation for curved members. In order to derive an adequate strength equation for curved members, this research suggests a new concept of ultimate state. Finite element analysis using ABAQUS is used to consider the effects of sectional rigidities for bending, pure torsion and non-uniform torsion separately. Finally, an ultimate strength equation is suggested for simply supported curved girders that are subjected to equal end moments.